Identificação do linfonodo sentinela pré-quimioterapia em câncer de mama localmente avançado e axila clinicamente negativa utilizando hemossiderina - Aguiar, Paulo Henrique Walter de (2018)
Introdution and objective: Evaluate the concordance rate in the identification of the sentinel lymph node in locally advanced breast cancer using an autologous marker and phytate labeled with technetium 99m. Method: The prospective, non-randomized phase 1 trial with 18 patients with locally advanced breast cancer and clinically negative axilla at the T> 4cm, T3 and T4 stage. Patients were submitted to subareolar injection of a hemosiderin-rich autologous marker 48 hours before the surgical procedure for sentinel lymph node biopsy (LNB) and the identification rate was compared intraoperatively with the technetium 99m radioactive marker (gold standard). The agreement rate between the methods was established by the Kappa index. Results: The identification rate was 88,9%, with an average of 2 sentinel lymph nodes (LN) per patient. The study identified hemosiderin-stained LN in 83.3% of the cases (15) when compared to the radiopharmaceutical identification rate in 94.4% of the cases studied (Kappa=0.77 and p=0.001. Age of the patient, size and location of the tumor and immunohistochemical factors did not interfere in the study outcome. Conclusion: The hemosiderin-rich autologous marker was found to be equivalent in the identification of sentinel lymph node in cases of patients with locally advanced breast cancer with clinically negative axilla.